Reason and Its Living Horizons in Edmund Husserl’s Phenomenology - Walton, Roberto J. (Investigaciones Fenomenológicas, 2021)
Husserl rejects the contrast between human life as an irrational factum and reason as an objectifying force that is hostile to life. Hence he moves away from the incompatibility between philosophy as science and philosophy of life. This paper has two purposes. First, it attempts to analyze the sequence of living horizons of reason, i.e., to lay out a progressive bringing-into-play that begins in a primal history linked to instinct, goes through history proper with its manners of practical reason, and reaches its culmination in a second historicity with a teleological development. In his last dated manuscript, Husserl speaks of “the upright, fair reason of the natural, sound human understanding” that plays a role before “the scientific, philosophical reason” (Hua XXIX, 386). Secondly, against this background, phenomenology of reason is considered as a view that is grounded in passive fulfillments, traces theory back to life, and emphasizes the interpenetration of the various manifestations of reason. It is argued that the relationship between intention and fulfillment pervades the movement from latent to manifest reason, renders possible different modes of rational legitimation, and shows distinctive traits in each mode. With regard to the vitality of Husserlian reason, a brief epilogue for the Spanish speaking world deals with some of J. Ortega y Gasset’s views on the issue. Husserl rechaza la contraposición entre la vida humana como un factum irracional y la razón como una fuerza objetivante hostil a la vida. Por eso se aparta de la incompatibilidad entre la filosofía como ciencia y la filosofía de la vida. Este trabajo tiene dos propósitos. Prime-ro, intenta analizar la secuencia de horizontes vitales de la razón, es decir, desplegar una progresiva puesta-en-juego que se inicia en la protohistoria ligada al instinto, pasa a través de la historia en sentido propio con sus modalida-des de razón práctica, y culmina en una segun-da historicidad con un desarrollo teleológico. En su último manuscrito fechado, Husserl habla de “la proba y honrosa razón del entendimiento humano natural” que desempeña un papel con anterioridad a “la razón científica, la filosófica” (Hua XXIX, 386). En segundo lugar, frente a este trasfondo, se examina la fenomenología de la razón como una visión que se funda en cum-plimientos pasivos, refiere la teoría a la vida, y pone énfasis en la compenetración de las varia-das manifestaciones de la razón. Se sostiene que la relación entre intención y cumplimiento atraviesa el movimiento desde la razón latente a la razón patente, hace posible diversos modos de legitimación racional, y muestra rasgos distintivos en cada uno de los modos. Respecto de la vitalidad de la razón husserliana, un breve epílogo para hispanoparlantes considera algu-nos puntos de vista de J. Ortega y Gasset sobre la cuestión.